The prognostic value of homocysteine levels in hemorrhagic stroke patients: a systematic review and meta-analysis - Yi Zong; Qiaohui Gu (Frontiers in Neurology)
BackgroundHemorrhagic stroke is associated with significant morbidity and mortality, prompting the search for modifiable risk factors and prognostic indicators. Elevated homocysteine levels have been implicated in vascular diseases, but their link to hemorrhagic stroke outcomes remains unclear. This systematic review and meta-analysis aimed to evaluate the association between homocysteine levels and outcomes in hemorrhagic stroke patients.MethodsThe MEDLINE, EMBASE, and Cochrane Central databases were searched for studies comparing the outcomes of hemorrhagic stroke in patients with high versus normal homocysteine levels. Data were pooled using random-effects models to calculate odds ratios (ORs) for mortality and poor functional outcomes and standardized mean differences (SMDs) for homocysteine levels, with respective 95% confidence intervals (CIs).ResultsThe review included 10 studies. Pooled analysis showed no significant association between high homocysteine levels and increased risk of mortality (OR: 1.123, 95% CI: 0.589 to 2.143), poor functional outcomes (OR: 1.203, 95% CI: 0.962 to 1.504), or unfavorable neurological outcomes (OR: 1.001, 95% CI: 0.618 to 1.620). Substantial heterogeneity was observed among studies.ConclusionHigh homocysteine levels were not significantly associated with mortality, functional outcomes, or unfavorable neurological outcomes in hemorrhagic stroke patients. The clinical utility of homocysteine as a prognostic marker in this population remains uncertain and warrants further research.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD42024527207.